Laporan Kasus: Pemeriksaan Forensik pada Kasus Kekerasan dalam Rumah Tangga (KDRT) - Putra, Anugrah Pratama; Mansyur, Mauluddin; Mathius, Denny; Assegaf, S. Zulfikar (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background: Domestic violence (DV) is a social and legal issue with far-reaching impacts on victims, including physical, psychological, and social consequences. Law No. 23 of 2004 concerning the Elimination of Domestic Violence (DV Law) serves as the legal foundation for efforts to protect victims of domestic violence. However, its implementation in practice continues to face challenges and has not yet proven fully effective in comprehensively preventing and addressing such cases. According to data from the Ministry of Women Empowerment and Child Protection from January to June 2025, there were 11,343 reported cases of violence in Indonesia. Of these, 85% of the victims were women, and 61% of the incidents occurred within the domestic setting. The number of reported cases in 2024 stood at 31.947 cases, showing an increase from 29.883 cases in 2023. This annual rise in reported violence reflects the growing urgency of the issue. Therefore, understanding domestic violence is crucial as a reflection of concern for human dignity and humanitarian values. Case Description: An 18-year-old woman with initials SAS, was taken to Centra Visum of Bhayangkara Hospital Makassar on May 5, 2025 after being abused by her father. On the morning of May 5, 2025, the victim was pushed by her father, causing her to hit a wall, and was then dragged into the street with her hair pulled. The victim reported that this was the first incident of physical violence, although the relationship between her and the perpetrator had been strained for the past year. The perpetrator consumed methamphetamine and had not provided financial support to the family for the past year. Physical examination revealed a bruise wound on the left side of the head, brush abrasions wound beneath the left eye and lower left cheek, and the right wrist, and scratch abrasions wound on the left knee and the inner front side of the right knee.